PENGARUH KUALITAS PELAYANAN PAJAK, SANKSI PAJAK DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Natalia Tutoq; Baharudin Saga (Jurnal Nusa Akuntansi, 2026)
This research aims to determine the influence of tax service quality, tax sanctions, and tax knowledge on motor vehicle taxpayer compliance. This research is a qualitative descriptive study with data collected using a questionnaire. The population in this study were motor vehicle taxpayers at the SAMSAT Gandaria City Outlet. The sample used in this research was 124 respondents obtained using the convenience sampling method. Data analysis in this research uses multiple linear regression analysis which includes data quality testing, classical assumption testing and hypothesis testing. The results of the analysis show that partially the quality of tax services and tax sanctions have a significant effect on taxpayer compliance, while tax knowledge does not have a significant effect on taxpayer compliance. The quality of tax services, tax sanctions and tax knowledge together or simultaneously influence taxpayer compliance at the SAMSAT Gandaria City Outlet.